Deciphering Squamous Cell Carcinoma Using Multidimensional Genomic Approaches - Ewan A. Gibb; Katey S. S. Enfield; Ivy F. L. Tsui; Raj Chari; Stephen Lam; Carlos E. Alvarez; Wan L. Lam (Journal of Skin Cancer)
Squamous cell carcinomas (SqCCs) arise in a wide range of tissues including skin, lung, and oral mucosa. Although all SqCCs are epithelial in origin and share common nomenclature, these cancers differ greatly with respect to incidence, prognosis, and treatment. Current knowledge of genetic similarities and differences between SqCCs is insufficient to describe the biology of these cancers, which arise from diverse tissue origins. In this paper we provide a general overview of whole genome approaches for gene and pathway discovery and highlight the advancement of integrative genomics as a state-of-the-art technology in the study of SqCC genetics.